The Times They Are Changing : Crisis and the Welfare State. - Greve, Bent (John Wiley & Sons, 2012)
The Times They Are Changing? Crisis and the Welfare State presents a series of readings from international policy researchers that examine the effects of the recent financial crisis on welfare states around the world. Provides comprehensive and in depth coverage of changes in welfare states as a result of the financial crisis Reveals how the financial crisis is changing our perception of the welfare statesFeatures contributions from policy researchers and academics from around the world.